Polymeric Nanosponges: A Promising Platform for Improving Roflumilast Solubility - Sarvesh Sharad Bagul,; Dr. Deepak D. Sonawane,; Mayuri P. Pol,; Dr. Sunil. K. Mahajan, (Asian Journal of Pharmaceutical Research and Development, 2026)
The drug roflumilast, a selective phosphodiesterase-4 enzyme inhibitor that can be used to treat persistent obstructive lung disease (COPD), has limited therapeutic potential due to its poor solubility and bioavailability. The aim of this literature review is to provide an overview of polymeric nanosponges as a novel drug delivery mechanism to enhance the solubility/bioavailability of roflumilast in vivo/vitro. Nanosponges are a type of nanocarrier that can be used to deliver poorly soluble drugs by encapsulating (i.e. solubilizing) these drugs—enhancing drug stability and providing zero order-controlled release. This review examines the fundamental properties of nanosponges including the different types of nanosponges, the preparation methods used to create them, and characterization methods. The role of nanosponges in improving the solubility of roflumilast by increasing surface area, molecular dispersion, and amorphous nature will also be discussed. Several formulation strategies and factors influencing the performance of nanosponges will also be covered. Finally, examples of in vitro and in vivo experiments that show improved solubility/bioavailability of roflumilast using nanosponges will also be presented in this review. In addition, advances in research related to targeted delivery, responsive to stimuli, and environmentally friendly synthesis of nanosponges will be discussed. Although there are barriers to the scale-up production of nanospounges and translational use in the clinic, the potential of polymeric nanosponges as a practical and versatile tool for advancing the therapeutic effectiveness of poorly soluble drugs like roflumilast is considerable.